2010
DOI: 10.4103/0971-6580.72682
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic system under aluminium toxicity in rat brain

Abstract: The present investigation envisages the toxic effects of aluminium on the cholinergic system of male albino rat brain. Aluminium toxicity (LD50/24 h) evaluated as per Probit method was found to be 700 mg/kg body weight. One-fifth of lethal dose was taken as the sublethal dose. For acute dose studies, rats were given a single lethal dose of aluminium acetate orally for one day only and for chronic dose studies, the rats were administered with sublethal dose of aluminium acetate once in a day for 25 days continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…Cholinergic neurons and acetylcholine are linked to learning, memory, movement and blood flow control in the brain [35]. Aluminium induces memory impairment by decreasing cholinergic function, as measured by acetylcholinesterase (AChE) and choline acetyltransferase activities, the key enzymes involved in the degradation and synthesis of acetylcholine [36]. Aluminum chloride treatment significantly increased aluminum concentration (Fig 4) and AChE activity (Fig 5) in hippocampus and cortex as compared to control rats.…”
Section: Resultsmentioning
confidence: 99%
“…Cholinergic neurons and acetylcholine are linked to learning, memory, movement and blood flow control in the brain [35]. Aluminium induces memory impairment by decreasing cholinergic function, as measured by acetylcholinesterase (AChE) and choline acetyltransferase activities, the key enzymes involved in the degradation and synthesis of acetylcholine [36]. Aluminum chloride treatment significantly increased aluminum concentration (Fig 4) and AChE activity (Fig 5) in hippocampus and cortex as compared to control rats.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the toxic effects of aluminium on the cholinergic system have been demonstrated in rats. Rats exhibited the typical symptoms of neurotoxicity, including hypokinesia, fatigue and seizures, parallelled by changes in the brain content of the two main constituents of the cholinergic system (acetylcholine and acetylcholinesterase activity) after the oral administration of sublethal doses of aluminium acetate (82) .…”
Section: Brain Pathologymentioning
confidence: 99%
“…Treatment with Al salts lead to elevation of neuronal AChE expression in rats (Olajide et al, 2017). Al interferes with cholinergic transmission and signaling, thereby, acetylcholine (Ach) metabolism is affected by Al (Yellamma et al, 2010). The present results showed that both the activity of brain AChE and plasma ChE were significantly elevated in Alzheimer model in rats that had intimate relation to learning and memory deficits after Al exposure (Kawahara, 2016).…”
Section: Discussionmentioning
confidence: 61%